2017
DOI: 10.3390/en10010065
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Performance for Wet Cooling Tower with Different Layout Patterns of Fillings under Typical Crosswind Conditions

Abstract: Abstract:A thermal-state model experimental study was performed in lab to investigate the thermal performance of a wet cooling tower with different kinds of filling layout patterns under windless and 0.4 m/s crosswind conditions. In this paper, the contrast analysis was focused on comparing a uniform layout pattern and one kind of optimal non-uniform layout pattern when the environmental crosswind speed is 0 m/s and 0.4 m/s. The experimental results proved that under windless conditions, the heat transfer coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Furthermore, the inclusion of experiments conducted after 201 sures that the table reflects the most recent advancements in cooling tower technology. Gao et al [20] Lu et al [21] Counterflow cooling tower Film-type fill Commercial corrugated packing with 98% porosity and dimensions: 5000 × 3300 × 2900 mm 3 ---Rahmati et al [22] Forced draft wet cooling tower Film-type fill, VGA (vertical grid apparatus), height of 95 cm PVC ---Singla et al [23] Counterflow forced draft cooling tower Expanded wire meshed fill ---…”
Section: Author Cooling Tower Type Configuration Materialsmentioning
confidence: 99%
“…Furthermore, the inclusion of experiments conducted after 201 sures that the table reflects the most recent advancements in cooling tower technology. Gao et al [20] Lu et al [21] Counterflow cooling tower Film-type fill Commercial corrugated packing with 98% porosity and dimensions: 5000 × 3300 × 2900 mm 3 ---Rahmati et al [22] Forced draft wet cooling tower Film-type fill, VGA (vertical grid apparatus), height of 95 cm PVC ---Singla et al [23] Counterflow forced draft cooling tower Expanded wire meshed fill ---…”
Section: Author Cooling Tower Type Configuration Materialsmentioning
confidence: 99%
“…For fully expressing the cooling capacity of tower, the Merkel number can be introduced, which has been widely applied in previous studies. The Merkel number is defined by Equation (26).…”
Section: Merkel Numbermentioning
confidence: 99%
“…The water surface temperature reduced by a maximum of 0.68 • C compared with no air duct. For making full use of the cooling capacity of the fill in a natural draft wet cooling tower, Zhou et al [25] and Gao et al [26] presented a non-uniform fill so that the height of the fill is higher in the air inlet, while lower in the center of the tower, and found that non-uniform fill improved thermal performance and decreased outlet water temperature, compared to uniform fill. Lye et al [27] also researched non-uniform fill in the wet cooling tower with high-level water-collecting devices, where the height of fill is higher in the center of the tower region and the height is lower in the air inlet.…”
Section: Introductionmentioning
confidence: 99%
“…Gao等人 [69] 对于涉及热湿迁移现象的空间非均匀 分布优化已经有了初步尝试, 布置方法示意图见图20, Figure 20 The ununiform layout of packing fills [69].…”
Section: 冷却塔优化设计及优化运行unclassified